Production and marketing of palay in Lambunao, Iloilo. - Pedroso, Ma. Arlene G
This study was undertaken to identify the cost and earning on the production and marketing of palay in Lambunao. The specific objectives of the study include: to determine the cost and returns in palay production and marketing; describe the production and marketing practices of palay; and to identify the problems of palay producers and middlemen., Forty-eight producer respondents were interviewed. Producers' average age was 49.47 years, average household size was 6.45 and farming experience average at 24.37 years. Secondary income sources of producers include livestock rearing and other farming related activities. Majority of the producers were land owners with land area of 26.5 ha, which represented 40.33 of the total palay area of 65.70ha. Producers earned positive gross and net profits. Producer-respondents were categorized according to tenurial status. Farm leasers obtained economic profit of P2,133.35, while farm owners and tenants received P812.02 and P1436.40 respectively. Farm leaser had the highest Rate of Return on Investment (0.50), while farm owners and tenants had 0.17 and 0.23 respectively. In terms of operating ratio, farm owners obtained a value of 0.76 which was relatively higher than that of farm lessers (0.39) and farm tenants. The costs of chemicals and fertilizer were the major problems of producers. Almost 100 of the farmers' produce were sold to the wholesaler -retailer at an average price of P5.82/kilo. Majority of the produce (92.10) were delivered to the market. The producers sold their produce mostly to their suki (40.35). Sources of price information includes buyers, prevailing market price and among the producers themselves. They received a net farm price of P4.86/kg. Two types of middlemen were identified namely the wholesaler-retailer and the commission men. However, only the wholesaler-retailer were interviewed. They availed 25,090 at P5.95/kg. They sold 2333.33kg outside Lambunao at P10.43/kg and the 470kg at 10.80/kg within the area. The factors considered in pricing palay were market price, trend in market, type and quality of palay.